2021
DOI: 10.1089/apc.2021.0050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an HIV Pre-Exposure Prophylaxis Referral System: From Sexual Health Center to Federally Qualified Health Center Pre-Exposure Prophylaxis Clinic

Abstract: Innovative delivery strategies are needed to facilitate access to HIV pre-exposure prophylaxis (PrEP). The objective of this study was to evaluate a navigator-facilitated PrEP referral process from a sexual health center (SHC) to a co-located PrEP clinic as an alternative delivery model. Electronic health record (EHR) data were used to calculate the number of clients seen at the SHC in 2019. Charts were manually reviewed to determine whether a PrEP clinic referral was made and document type of referral method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Stephanie Cohen and Oliver Bacon). In Chicago and New Orleans, despite warm handoffs via PrEP navigators or public health staff to an external PrEP provider, only 31% and 43% of referred patients attending an initial PrEP visit attended a subsequent PrEP visit 34,35 ; this high level of discontinuation occurred even when the PrEP clinic was separate but colocated with the SHC in New Orleans. Our experience suggests that rapid PrEP initiation provided as part of routine SHC visits and flexible demedicalized follow-up may help to engage and retain patients on PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Stephanie Cohen and Oliver Bacon). In Chicago and New Orleans, despite warm handoffs via PrEP navigators or public health staff to an external PrEP provider, only 31% and 43% of referred patients attending an initial PrEP visit attended a subsequent PrEP visit 34,35 ; this high level of discontinuation occurred even when the PrEP clinic was separate but colocated with the SHC in New Orleans. Our experience suggests that rapid PrEP initiation provided as part of routine SHC visits and flexible demedicalized follow-up may help to engage and retain patients on PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…This would also include studies related to health services and implementation science, which greatly contribute to the application and understanding of STI and HIV prevention management in real world settings. [51][52][53][54][55] Sentinel surveillance for STIs and HIV is a critical public health function incorporated into many SHCs. Sentinel surveillance involves the ongoing and systematic collection of case data from a sample of providers (in this case, SHCs) to identify trends in STIs in the larger population.…”
Section: Shcs Provide Specialty Services To Priority Populationsmentioning
confidence: 99%
“…Peer navigation has the potential to bridge these gaps in testing and treatment by increasing timely linkage to care. Lillis et al [63] demonstrated short-term increases in PrEP appointments in a sexual health clinic when a peer navigator was available for a warm handoff compared to those who received a referral from a provider or an E-Mail from peer navigators. Sevelius et al [64 ▪ ] developed and implemented a sex-affirming PrEP program for transgender adults at two healthcare centers, demonstrating the potential of co-locating peer navigation and gender affirming care in existing healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies published within this past year evaluated interventions premised on co-locating services to enhance uptake and use of HIV prevention and treatment technologies [62,63,64 ▪ ,65]. Lipps et al [62] integrated infectious disease specialists within emergency departments to increase HIV and STI testing and treatment and to provide additional training, resources, and timely support to medical providers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation